Adição de ácido fumárico em dietas elaboradas com silagem de grãos úmidos de milho: conservação de dietas, desempenho de porcas e leitegadas - Lehnen, Cheila Roberta (2009)
The objective of this study was to evaluate the preservation and effect of lactation diets with high moisture corn containing fumaric acid on the performance of lactating sows and their piglets. Twenty sows of commercial genetic lines were used in a randomized complete block with four treatments (basal diet -BD, elaborated each 24 h; BD + 0.3% of fumaric acid - FA; BD + 0.6% FA and BD + 0.9% of FA) with five replications each. Diets with fumaric acid were elaborated each 48 hours. The acidification of diets was 14% higher (P<0.01) in diets elaborated with high-moisture corn containing 0.9% of fumaric acid. The temperature in 48 hours after the elaboration of diets was 8% lower (P<0.01) in diets containing 0.9% of fumaric acid than basal diet. The addition up to 0.9% fumaric acid reduces the pH of diets. Fumaric acid reduces the temperature of diets from 24 hours after its elaboration. The average daily food intake of lactating sows was 7.42 kg of natural matter not influenced (P>0.05) by treatments. The 0.9% of fumaric acid addition in diets reduces in 6% (P<0.01) the pH of milk. The average daily weight gain and average weaning live weight of piglets were not influenced (P>0.05) between treatments. The addition of fumaric acid in diets does not alter the performance of lactating sows and piglets, but increases (P<0.05) the normal feces frequency in piglets. Based on the assessment of pH and temperature, it is possible to preserve diets elaborated with high moisture corn until 48 hours after the production with the addition of 0.9% of fumaric acid. The addition of fumaric acid in the diet improves the health condition of piglets in the nursery.